Traditional Chinese medicine therapy reduces the catheter indwelling risk in dementia patients with difficult voiding symptoms. (5th May 2017) - Lin, Shun-Ku; Lin, Po-Hung; Hsu, Ren-Jun; Chuang, Heng-Chang; Liu, Jui-Ming
Abstract: Ethnopharmacological relevance: Dementia is an international health issue in elder people. Indwelling catheters to address voiding problems in patients with dementia introduce risks of urinary tract infection or urethral trauma. Traditional Chinese medicine (TCM) is widely used to treat difficult voiding symptoms in Taiwan. We investigated the long-term clinical effects of TCM for reducing the risk of indwelling catheterization in dementia patients with difficult voiding symptoms. Materials and methods: We used National Health Insurance Research Database to conduct a retrospective study of dementia patients with difficult voiding symptoms between 1997 and 2012 in Taiwan. We collected medical data from the onset of dementia to post-catheter insertion. Cox regression proportional hazards model and cumulative incidence of the urinal catheterization curve were used to determine the association between catheter indwelling risk and TCM use. Results: Data from 11069 patients with dementia was assessed, and 3982 participants who received medication for relief voiding symptoms were categorized into 2 groups: 2121 (53.3%) were TCM users and 1861 (46.7%) were TCM non-users with a mean follow-up period of 7.25 years. Cox regression demonstrated that using TCM may decrease the need for indwelling catheterization in patients with dementia (adjusted hazards ratio (aHR) =0.58, 95% confidence interval (95% CI): 0.52–0.66) compared to TCM non-users. A relationship between longer TCM use and reduced urinary retention with indwelling catheter use was observed, especially in patients who used TCM for ≥200 days (aHR =0.46, 95% CI: 0.39–0.55). Ji-Sheng-Shen-Qi-Wan (aHR =0.44, 95% CI: 0.21–0.88), Wu-Ling-San (aHR =0.47, 95% CI: 0.16–0.92), Zhi-Bai-Di-Huang-Wan (aHR =0.50, 95% CI: 0.26–0.94), were the most 3 beneficial TCM formulae. Conclusions: The results of this study suggest that TCM is associated with a reduced risk of indwelling catheterization in patients with dementia, with enhanced benefits from longer durations of TCM use. Graphical abstract: The cumulative incidence of urinal catheterization in TCM users was significant lower than in non-TCM users. TCM use ≥200 days was associated with the lowest rates of catheterization, compared to non-TCM users in patients with dementia and difficult voiding symptoms (log-rank test, p <0.001).